Catalysts in action: decomposition of hydrogen peroxide - A. M. R. Rocha, Jorge (2024)
The present work demonstrates the application of chemical and biological catalysts in the decomposition reaction of hydrogen peroxide – H2O2. This compound is quickly degraded by metal catalysts or by the catalase enzyme present in aerobic organisms. Hydrogen peroxide decomposition experiments were carried out using metallic catalysts and enzymatic catalysts, catalase, contained in some tubers or baker’s yeast. Inhibition and denaturation experiments on the catalase enzyme were also carried out. Using cheap and widely available materials, in easily performable experiments, it is possible to demonstrate the action of catalysts, chemical or biological, performing the decomposition of H2O2 through the production of oxygen gas bubbles.